1978
DOI: 10.1111/j.1745-4565.1978.tb00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lead Concentration of Foods Stored in Their Opened Cans

Abstract: A study was made of the effect on the concentration of lead in canned fruits and juices when these food products are stored in their original containers after opening. Samples stored in a refrigerator were analyzed for lead upon initial opening, 2 days after opening, and 5 days after opening. Products in nonlacquered cans showed significant increases in lead concentration with time. The increase of lead in the food product could have an effect on estimates of average dietary intakes of lead if this practice is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…Diluted digest solutions were analyzed for Pb by differential pulse anodic stripping voltammetry. The results for Pb have already been reported (Capar 1978). Subsequently, multielement analyses were performed using inductively coupled argon plasma (ICAP) emission spectroscopy and are reported in this paper.…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…Diluted digest solutions were analyzed for Pb by differential pulse anodic stripping voltammetry. The results for Pb have already been reported (Capar 1978). Subsequently, multielement analyses were performed using inductively coupled argon plasma (ICAP) emission spectroscopy and are reported in this paper.…”
Section: Methodssupporting
confidence: 83%
“…Available corresponding glass-packed products were used as controls. A description of the samples, the sampling procedure, and the sample mineralization were described previously (Capar 1978). Briefly, the products were sampled from their containers upon initial opening, 2 days after opening, and 5 days after opening.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…The increases in lead levels observed in this study for foods stored in open cans are in agreement with the work presented by others. Those products in the present study which we had studied previously (Capar 1978) showed similar increases in lead levels, except for Tomato Juice. In the previous preliminary study the lead levels in Tomato Juice increased slightly (i.e., to two times the Day-0 level) between Day4 and Day-5 as opposed to a significant increase to 11-16 times the Day-O level in the present study.…”
Section: Fig 1 Relative Lead Levels For Products Showing Sionificansupporting
confidence: 78%
“…Besides the lead that is added to the food while it is stored in a sealed can, there is information indicating that the leaching of lead from the can is accelerated by some foods after the can is opened. Early studies on the leaching of lead from opened cans concerned baby foods (Kimura et al 1970;Lee et al 1975); however, the packaging of baby foods in lead-soldered cans has been discontinued, and recent studies have dealt with adult foods eaten by children (Capar 1978;Environmental Research Group 1980;Ellis et al 1983). Because acid foods such as fruit juices appear to leach the most lead, the FDA has advised against storing such acidic foods in opened cans (FDA 1981).…”
Section: Introductionmentioning
confidence: 99%